Grief experience among ICU staff with loss of family members during COVID-19 outbreak in IRAN: A qualitative study - Nohesara, Shabnam; Saeidi, Mahdieh; Mosavari, Hesam; Ghalichi, Leila; Alebouyeh, Mahmoud Reza (Frontiers in Psychiatry, 2022)
The Covid-19 crisis created a lot of complexities in people’s lives. Different lifestyles, mental well-being, communication, rituals and traditions, particularly those involved in mourning, have changed drastically. Medical staff were facing numerous patients every day who were dying from this disease. This distressed the medical staff, especially ICU staff, greatly. This ended up in huge amounts of mental distress for the medical staff who lost a loved one to Covid-19 the distress became even more complex. We carried out this qualitative research to study the different grief experiences of 12 Iranian ICU staff members in Rasoul Akram Hospital, who had experienced the loss of a loved one during Covid-19. We studied the effects of how the grief experience influenced their work with patients and how constant exposure to critically ill patients influenced their own grief experience. All semi-structured interviews were held in the presence of a faculty member of the psychiatry department of Iran University of Medical Sciences. The interview on the experience of death contains 4 sections: familiarity, various experiences during the pandemic, grieving the loss of the loved one, and effects of parallel grieving. We found five common themes in the result of the experiences of the participants. These consisted of: complex grieving process, new experiences for coping with loss, more empathy for patients, different meanings of death, and the need for the support of various workplaces. Likewise, there were twenty-two sub themes. Paying attention to the details of a staff’s life, the gender differences, and cultural aspects can give us a better understanding and perception of their grief experiences. This understanding brings out valuable points which can help policy makers of countries pass better laws for the well-being of the society and people in a way to promote leadership in turbulent times.